孫世代が担う高齢者介護 - 横瀬 利枝子 (生命倫理, 2016)
Many of the participants in this study were either those who had one of their parents passed away or suffering from a disease or those whose parents were nursing each other, so the participants, who were grandchildren, were taking care of their grandparents all by themselves. The nursing-care insurance, while available, provides only limited benefits if there is a family member living together, and the distressing situation is left unattended especially for younger-generation caretakers. Meanwhile, none of the participants was receiving any livelihood subsidies for economic support but was in needy conditions, as they felt solitude and estrangement as well as uncertainty for the future. They had little association with the same generation. Therefore, it would be our pressing task to grasp the existence of these younger generation caretakers, starting from our own backyard such as schools, communities, etc. so that those who have difficulty in participating in family functions may not be isolated from society to have their future closed in or they may not have themselves isolated. Support to care for younger generation caretakers must be given urgently in such a way as to cause no new stigma as we respect and value the feelings of the younger generation 本研究では協力者の多くが父や母を亡くしているか、父母のいずれかが病を抱えており、両親が揃っていても互いの介護を担っているため、孫に当る協力者がひとりで、祖父母の介護責任を負っている。介護保険も同居家族がいることで援助範囲が制限されるなど状況は厳しいが、若年介護者の窮状は見過されている。一方、経済的には各協力者とも生活保護などは受けていないが厳しい状況であり、孤独感や疎外感を懐き、将来への不安を感じている。同世代との繋がりも難しく、家族の会への参加も困難な若年介護者が、社会から孤立して将来を閉ざされたり、自ら閉ざさぬよう、学校、地域など身近な所から、若年介護者の存在を把握することも喫緊の課題であろう。若年介護者の想いを尊重し擁護しながら、新たなスティグマをうみ出さぬよう、若年介護者に寄り添う支援の創出が急がれる。